Blaise Cendrars and Brazil: Brésil, des hommes sont venus - Wimmer, Norma (Lettres Françaises, 2013)
The paper intitled Blaise Cendrars and Brazil: Brésil, des hommes sont venus discusses the way Cendrars portrays Brazil, and also debates his influence on the artists of the Semana de Arte Moderna (Modern Art Week) in 1922.